Performance analysis of a floating breakwater integrated with multiple oscillating water column wave energy converters in regular and irregular seas. (June 2020) - Howe, Damon; Nader, Jean-Roch; Macfarlane, Gregor
Abstract: Maritime structure integration is widely considered as a potential solution for reducing the high Levelised Cost of Electricity (LCOE) associated with Wave Energy Converter (WEC) technologies. However, the majority of published research has focused on fixed structure integration [1, 2], with far fewer investigating the potential for floating structure integration [3]. Expanding on previous works [4, 5], this article investigates the performance of a π -type floating breakwater integrated with multiple Oscillating Water Column (OWC) WECs through model scale hydrodynamic experimentation. While under varying structural arrangements including device configurations and motion constraints, the model was subjected to 13 generic irregular wave spectra. Results of the experimental investigation illustrate that OWC device integration provides distinct benefits to the non-dimensional performance parameters of the floating breakwater in irregular sea states, which correlates strongly with the results obtained from previous regular wave analyses [4, 5]. With firm correlation between the regular and irregular analyses, it is hypothesized that device development could potentially forgo regular wave investigations in preference of irregular wave testing, as it yields a broader bandwidth of results with reduced temporal requirements. Similarly, it is illustrated that the irregular non-dimensional parameter spectra can be used to effectively predict the performance characteristics of the device across different sea states. This article furthers the concept validation and feasibility of OWC WEC integrated floating breakwaters, and aids in the progression of the concept through the Technology Readiness Levels.